(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2018)
The current state of the Debed Rriver basin system has been analyzed and assessed, anthropogenic pressures on water resources have been discussed, the super objectives of the sphere have been analyzed and clarified mechanisms for effective use and protection of water resources have been proposed.